Study of Eco-Enzyme Application in Reducing Nitrite Concentration and Ph Value in Water Sample - Wikaningrum, Temmy; Resda, Cicilya Dolfiana (Universitas Batanghari Jambi, 2024)
The number of high fruit loss must be resolved immediately. East Java produces the highest number of banana and orange. To prevent the fruit loss, as mitigation, the fruit loss can be used to make eco-enzymes as biodegradable agents which was made from nature to treat contaminated water from nitrite contamination and high pH value. Contaminations such as nitrite in water pose significant risks, particularly to organisms. Nitrite contamination can adversely affect humans by reacting with hemoglobin, leading to the formation of methemoglobin, which hampers the blood's ability to bind with oxygen and transport it to body tissues. Eco-enzymes serve as biocatalysts to accelerate the nitrification process, converting ammonia into nitrate with nitrite as an intermediate product. This study was conducted on a laboratory scale, using water samples comprised of distilled water and nitrite standard solution. Two types of eco-enzymes, derived from banana and orange waste, were applied at a 5% concentration to reduce nitrite levels and pH values in the water samples. The results indicated that the orange eco-enzyme reduced nitrite concentrations by 73.2% and pH values by 38.42%, while the banana eco-enzyme achieved a reduction of 93.89% in nitrite concentrations and 23.15% in pH values. As an application of this study, the 5% eco-enzyme solution holds promise for use in biological treatment within wastewater treatment plants, particularly in aeration tanks, to enhance the nitrification process, thereby aiding in the reduction of nitrite concentrations and pH values in wastewater.